The Northernmost Occurrence of the Tropical-Subtropical Brittle Star Ophiocoma (Echinodermata, Ophiuroidea) from a Late Cretaceous Rocky Shore in Southern Sweden - Ben Thuy; Lea D. Numberger-Thuy (Taxonomy, 2023)
In spite of considerable progress during the last few years, the fossil record of the ophiuroids, or brittle stars, is still poorly known, especially with respect to taxa restricted to specific environments. Here, we describe new ophiuroid fossils collected from an Upper Cretaceous rocky shore in Ivö Klack, southern Sweden, consisting of fully disarticulated skeletal remains retrieved from the sediments deposited between boulders and hummocks. The fossils are identified as a new species of the extant ophiocomid genus Ophiocoma. In a critical revision of the ophiocomid fossil record, we show that all fossils previously assigned to the Ophiocomidae belong to other families. Thus, the fossil record of the Ophiocomidae is currently restricted to the new species described herein, and Amphiura? gigantiformis from the Miocene of Austria which, in fact, is a species of Ophiocoma. Since recent species of Ophiocoma exclusively occur in tropical to subtropical shallow subtidal environments, our discovery of a fossil Ophiocoma species in the rocky shore sediments of Ivö therefore conforms with the previously assumed subtropical palaeotemperatures prevailing in southern Sweden during the Late Cretaceous. Most notably, it represents the northernmost occurrence of an ophiocomid recorded to date.